Herbicidal efficacy and selectivity of goal in potato (Solanum tuberosum L.) in the Northern State, Sudan - A. M. Bedry, Kamal; El Habieb, R. Y.; Ahmed1, M. A.; Abdellatif, I. A. (Gezira Journal of Agricultural Science, 2023)
Experiments were conducted at Elsaggai and Merowe, Northern State, Sudan, during the period  2007 to 2009 to assess the damage inflicted by weeds on potato and  determine herbicidal efficacy and selectivity of the herbicide Goal (oxyfluorfen) in potato in the Northern State. Unrestricted weed growth reduced potato total and marketable yields by 50% - 84% and 54% - 97%, respectively. Goal at all rates and times of application reduced weed air-dry weight by 26% - 97%. It resulted in excellent early and late season control of grassy weeds. However, Cynodon dactylon (L.) Pers and Cyperus rotundus L. were not affected. Goal at all rates applied 7 and 14 days after planting (DAP) effected excellent (83% to 98%) and moderate (48% to 67%) late season control of broad-leaved weeds at Elsaggai and Merowe. Goal increased total and marketable tuber yields by 14% - 100% and 40% - 200%, in both locations respectively, over the unweeded control. The herbicide at 0.3 kg a.i/ha applied 7 DAP resulted in excellent (96% - 99%) and persistent control of annual grassy weeds and gave adequate (66% to 100%)  control  of  broad-leaved weeds. It increased total and marketable tuber yields by 59% to 100% and 82% to 200%, respectively, over the control and is safely recommended for weed management in potato in the Northern State.